MASYARAKAT HUKUM ADAT PASKA PUTUSAN MAHKAMAH KONSTITUSI 35: ANTARA REKOGNISI DAN MARGINALISASI - L.R Wibowo; M Budi Mulyawan; Yustina Ambarini M; Ismatul Hakim (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2018)
The Kandayan Dayak is one of the customary community (MHA) which has been hereditary living in the forest area of ​​West Kalimantan province. The Kandayan has rules and local wisdom in managing natural resource that have long been inspired by the ancestors, but their legal status of their residence and customary land area overlaps with the area of ​​forest timber forest product utilization (UPHHK-HTI) and oil palm plantations. The uncertainty of the ulayat rights made the Kandayan customary to move to areas outside the limited production forest controlled by UHHK-HTI. The limitations to access natural resources make these indigenous peoples have tocollaborate with local entrepreneur through profit-sharing mechanism. Along with this partnerships, they are losing the livelihood resources that have so far sustained their survival and they are also uprooted from the bonds of cultural relations with their land. In other words their sovereignty over the right of forest resources becomes eroded by excessive capitalization by the modern forest industry